Medication adherence and predictive factors in patients with cardiovascular disease: A cross‐sectional study. (8th January 2020) - Al‐Ganmi, Ali Hussein Alek; Alotaibi, Abdulellah; Gholizadeh, Leila; Perry, Lin
Abstract: Adherence to cardiac medications makes a significant contribution to avoidance of morbidity and premature mortality in patients with cardiovascular disease. This quantitative study used cross‐sectional survey design to evaluate medication adherence and contributing factors among patients with cardiovascular disease, comparing patients who were admitted to a cardiac ward ( n = 89) and those attending outpatient cardiac rehabilitation ( n = 31) in Australia. Data collection was completed between October 2016 and December 2017. Descriptive and regression analyses were conducted to identify medication adherence and determine factors independently predictive of medication adherence. Participants from cardiac rehabilitation had significantly lower adherence to cardiac medications than those recruited from the cardiac ward (58.1 vs 64.0%, respectively). Self‐efficacy was significantly associated with participants' medication adherence in both groups. The ability to refill medications and beliefs about cardiac medications were independently significantly predictive of cardiac medication adherence. These findings indicate areas where clinical nurses could expand their role to improve cardiac patients' medication self‐management.